PENIPUAN BERBASIS SKEMA PIRAMIDA: TINJAUAN MENURUT KUHP - Thoriq, Muhammad; Jainaya, Kapiya; Azhar, Bintang; Firmansyah, Alif; Antoni, Herli (LPPM, Universitas Muhammadiyah Riau, 2025)
Pyramid scheme-based fraud is a form of economic crime that is increasingly occurring in Indonesia. This fraud has a mode where the perpetrator takes advantage of large profits quickly through recruiting new members. This criminal scheme is basically unsustainable and has the potential to harm many parties, especially participants at lower levels or levels. This research aims to analyze pyramid schemes as a form of fraud from the perspective of criminal law in Indonesia, especially from the perspective of the Criminal Code (KUHP). The method used is a normative juridical approach by analyzing relevant articles, such as Article 378 of the Criminal Code concerning criminal acts of fraud, as well as making comparisons with other more specific regulations such as the Consumer Protection Law and Financial Services Authority (OJK) regulations. The results of the analysis show that even though the Criminal Code does not explicitly regulate pyramid schemes, the elements in Article 378 of the Criminal Code can be imposed on the perpetrator, knowing that the perpetrator has the intention to obtain profits for themselves unlawfully by deceiving other people. There is a need for more comprehensive legal updates or implementing regulations in order to provide legal certainty and protection to the public from fraudulent acts under the guise of investment.